2014
DOI: 10.1002/cphc.201301032
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Fluorescently Labeled Triethyleneglycol and Peptide Derivatives with β‐Cyclodextrin

Abstract: A triethyleneglycol (TEG) chain, a linear peptide, and a cyclic peptide labeled with 7-methoxycoumarin-3-carboxylic acid (MC) and 7-diethylaminocoumarin-3-carboxylic acid (DAC) were used to thoroughly study Förster resonance energy transfer (FRET) in inclusion complexes. (1) H NMR evidence was given for the formation of a 1:1 inclusion complex between β-cyclodextrin (β-CD) and the fluorophore moieties of model compounds. The binding constant was 20 times higher for DAC than for MC derivatives. Molecular modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…All of these results highlight that our doubly-labeled peptides formed a 1:1 supramolecular assembly through only their DAC moiety with the β-CD support, as expected from the previous studies in solution. 20 Due to similar peptide structure and our previous published data in solution 20 of these peptides (SMMP-1, 2 and 9), we expect that Ka values for SMMP-2 and SMMP-9 are in the same range than for SMMP-1. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 To validate the sensor regeneration, a supramolecular assembly between β-CD modified SAW SAM ® 5 chip and SMMP-1 (500 µM) was performed.…”
Section: Supramolecular Assembly Studymentioning
confidence: 80%
See 3 more Smart Citations
“…All of these results highlight that our doubly-labeled peptides formed a 1:1 supramolecular assembly through only their DAC moiety with the β-CD support, as expected from the previous studies in solution. 20 Due to similar peptide structure and our previous published data in solution 20 of these peptides (SMMP-1, 2 and 9), we expect that Ka values for SMMP-2 and SMMP-9 are in the same range than for SMMP-1. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 To validate the sensor regeneration, a supramolecular assembly between β-CD modified SAW SAM ® 5 chip and SMMP-1 (500 µM) was performed.…”
Section: Supramolecular Assembly Studymentioning
confidence: 80%
“…Recently, we have reported that our biscoumarinic MMP substrates interact with β-CD in solution and form only a stable supramolecular complex between diethylaminocoumarin (DAC) and β-CD. 20 These results highlight intrinsic property of our peptides to potentially form supramolecular assembly with a β-CD surface. To tackle the challenges related to both MMP 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 5 activity screening and biosensor development, we present an innovative supramolecular peptide sensor for screening in vitro and ex vivo MMPs activities ( Figure 1).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…photoresponsive supramolecular systems are widely studied [12,13], especially in the case of interlocked structures [14][15][16]. A few studies have been published on the effect of cyclodextrins on the fluorescence behavior of FRET dyads in aqueous solutions [17,18], however the modulation of FRET in covalently linked donor-acceptor pairs by supramolecular interactions is virtually unexplored. In the present work we studied this effect on the example of a complex formed by a stilbazolium dyad (G) and a pillararene macrocycle.…”
Section: Introductionmentioning
confidence: 99%